2015
DOI: 10.1371/journal.pone.0116744
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Anti-Muscarinic Receptor Type 3 Antibodies for the Diagnosis of Sjögren Syndrome

Abstract: PurposeTo conduct a meta-analysis to evaluate the diagnostic value of anti-muscarinic receptor type 3 (M3R) antibodies in Sjögren syndrome (SS).MethodsTwo databases, PUBMED and the Cochrane Library, were systematically searched. Approximately 2,000 participants from several studies were included in this research. STATA 11.2 software and Meta-DiSc 1.4 was used to conduct the meta-analysis.ResultsEleven studies were included in the meta-analysis. The pooled DOR was 13.00 (95% CI, 6.00–26.00). The sensitivity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Antinuclear antiboides, anti‐Ro positivity and low complements were more common in Asian populations. Higher sensitivity of anti‐muscarinic receptor type 3 and anti‐α‐fodrin antibodies were reported in Asian patients with pSS . It has also been shown that cryoglobulinemia is less prevalent in Asians .…”
mentioning
confidence: 98%
“…Antinuclear antiboides, anti‐Ro positivity and low complements were more common in Asian populations. Higher sensitivity of anti‐muscarinic receptor type 3 and anti‐α‐fodrin antibodies were reported in Asian patients with pSS . It has also been shown that cryoglobulinemia is less prevalent in Asians .…”
mentioning
confidence: 98%
“…However, the functional data have not been reconciled with the sensitivity and specificity of the anti-M3R autoantibodies in screening trials [ 10 ]. Although anti-M3R autoantibodies have been detected in 9–100 % of SS patients depending on the method and antigens used [ 34 ], a recent meta-analysis study concluded that the anti-M3R antibody has high specificity (0.95) but relatively low sensitivity (0.43) to diagnose SS [ 35 ]. In this aspect, the anti-AQP5 autoantibodies identified in the current study could complement anti-M3R autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It is suspected that antibodies towards M3R may potentially inhibit saliva secretion . Some have reported a 60–80% concordance of anti‐M3R with Sjögren's syndrome but the usage has been hampered by reproducibility issues and anti‐M3R is therefore not widely used as a biomarker in clinical settings. Improvement in analytical techniques may change this.…”
Section: Diagnostic Markers In Serum/plasma For Primary Sjögren's Synmentioning
confidence: 99%